Functional-semantic features of the interrogative pronouns who and what (Eurasian Research Bulletin, 2023)
With the feature of pronouns, it cleans our speech from redundant repetitions and provides a concise statement of the idea. Each word has its own meaning. This is a lexical meaning. Although the lexical meaning is a whole semantic whole in the content plan of the lexeme, later it is determined that this whole contains certain parts of meaning - semes. Atash schemas (denotative schemas), expression, image additional meaning schemas (connotative schemas), task schemas (functional schemas).